A bimodal endoscopic imager in a glass package. (11th July 2018) - Kretschmer, Simon; Jäger, Jan; Vilches, Sergio; Ataman, Çağlar; Zappe, Hans
Abstract: We present the first endoscopic imaging probe that combines full-field white light video microscopy and 3D optical coherence tomography (OCT) in a single miniaturized instrument. Designed as an instrument for the working channels of conventional endoscopes, the presented system has dimensions of mm 3 (l  ×  w  ×  h) and is an important step towards practical multi-modal optical biopsy systems for clinical use. The video modality has a sensor-limited resolution and a total field of view of 10 μ m and 1.17 mm in diameter, respectively. The OCT modality works in a scanned imaging arrangement and provides 3D optical tomograms with a lateral resolution of 43.5 μ m. An integrated tubular piezoelectric fiber scanner is used to perform en face scanning necessary for the 3D OCT measurements. The entire system is assembled and encapsulated within a glass package fabricated via 3D laser microstructuring, a technology which addresses the major issues of micro-optic assembly precision and biocompatibility.